2023
DOI: 10.1177/20420986231181337
|View full text |Cite
|
Sign up to set email alerts
|

Joint use of population pharmacokinetics and machine learning for optimizing antiepileptic treatment in pediatric population

Ivana Damnjanović,
Nastia Tsyplakova,
Nikola Stefanović
et al.

Abstract: Purpose: Unpredictable drug efficacy and safety of combined antiepileptic therapy is a major challenge during pharmacotherapy decisions in everyday clinical practice. The aim of this study was to describe the pharmacokinetics of valproic acid (VA), lamotrigine (LTG), and levetiracetam (LEV) in a pediatric population using nonlinear mixed-effect modeling, while machine learning (ML) algorithms were applied to identify any relationships among the plasma levels of the three medications and patients’ characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In pharmacokinetics, machine learning allows for analysis and prediction ( Ota and Yamashita, 2022 ; Wang et al, 2023 ). The combination of machine learning and population pharmacokinetics is a new tool for drug research and development ( Zhu et al, 2022 ; Damnjanovic et al, 2023 ). It has been reported that machine learning combined with PPK method can improve the prediction of individual clearance of six drugs in neonates ( Tang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pharmacokinetics, machine learning allows for analysis and prediction ( Ota and Yamashita, 2022 ; Wang et al, 2023 ). The combination of machine learning and population pharmacokinetics is a new tool for drug research and development ( Zhu et al, 2022 ; Damnjanovic et al, 2023 ). It has been reported that machine learning combined with PPK method can improve the prediction of individual clearance of six drugs in neonates ( Tang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the prediction of individual drug concentrations has a crucial impact on finding the optimal dosage regimen and, eventually, on therapeutic success. Interest Pharmaceutics 2024, 16, 358 2 of 19 in augmenting pharmacokinetic models with the help of machine learning algorithms has recently increased because the construction of models which efficiently represent a broader set of patients has often proved to be an overwhelming task, especially in pediatric populations, as well as in populations diagnosed with rare diseases, or living with special conditions (e.g., oncological and organ-transplant recipients, or patients receiving intensive care) [6][7][8][9]. Augmented pop-PK models are expected to overcome the limitations posed by the availability of a low number of subjects and/or data points, and may therefore facilitate the implementation of MIPD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the higher accuracy of ML algorithms, there are some limitations to this strategy, such as inexplicable results (Destere et al, 2023). It can be assumed that a proper combination of two methods may provide more reliable predictions (Damnjanović et al, 2023). This study aimed to establish a model of TAC ML combined with PPK in Chinese patients undergoing renal transplantation.…”
Section: Introductionmentioning
confidence: 99%